"What can you do with a Story Like This[?]": The Expectations and Explicitations of South African Fiction. Issue 2 (3rd July 2019) - de Villiers, Rick
Abstract : The question – "how does fiction respond to nonfiction?" – implies several others. One has to do with a special kind of mimesis and asks whether formal aspects of the 'documentary' mode are directive for fictional modes. Another question pertains to motives. This article addresses the latter, but with an eye on criticism itself. It argues against instrumental readings that promote aesthetic values on the basis of ethical values, not because this is inherently problematic, but because such an approach risks neglecting the degree to which fiction and nonfiction alike partake in mimetic strategies that promote a 'truth-effect' with compelling and sometimes troubling immediacy. Without positioning it as representative of "fiction's response", Damon Galgut's In A Strange Room is considered here as exemplary in its ability to disrupt the charms of mimesis through its estranging use of punctuation, self-representation, and intertextuality.